The Impact of ICT on Career Counseling Services: A case Study of Nigerian Secondary Schools - Obi M. C.; Oye N. D.; Mohd T. N.; Bernice A. (International Journal of Evaluation and Research in Education (IJERE), 2012)
Information and communication technologies (ICT) will need to be fully integrated into the delivery of careers services as the world is now in the global era. Such integration would not only have the potential to achieve more but would also increase the flexibility of services and enhance their quality. Career choice is an  important  decision  a  person  needs  to  make  in  his  life  time.  Unfortunately, many young people find it uneasy to make appropriate career choice. The  paper  focused  on  the  usage  of  career  counseling  services  in  selected public secondary schools in Nigeria. It sought to find out how students and teachers utilize  career  counseling  services,  students’  expectations  in  career  counseling services  and  how  school  principals  support  career  counseling  services.  Simple random  sampling  was  used  to  select  380  from 34  public  secondary  schools  from  the  sample  population.  Four-point Likert scale questionnaires were used to obtain data for the study. The findings revealed that the students use career counseling services to take career decision and aspiration, gather career information and select and take subjects that match their career interest. Secondary school teachers use career counseling services to guide students to make appropriate subject choice that match their career interest and help them with their career challenges and plans. This paper recommends that career counselors should integrate use of ICT, through the use of chat rooms, email and social networking. In other words several choice of career could be show to the students on DVD and CD Video. They should also be exposed to TV and radio Chat on Career choice.DOI: http://dx.doi.org/10.11591/ijere.v1i1.709